Estudo ecológico do câncer de próstata em mesorregiões do estado do Pará - ALVES, João Victor Moura (2023)
Introduction: According to the WHO, in 2018, cancer was responsible for almost 10 million deaths, with approximately 70% of these occurring in low- and middle-income countries. Unlike incidence, mortality rates are more present in less developed regions. Prostate cancer is the most common type of cancer among men in different regions of Brazil, behaving as an important public health problem around the world. Thus, this study aims to study epidemiological aspects of prostate cancer, based on an ecological study in mesoregions of the state of Pará. Objectives: To investigate the distribution of cases and deaths, as well as to analyze the trend of cases/mortality, from prostate cancer, in the State of Pará, from January 2017 to December 2020. Methodology: Epidemiological, ecological study to describe the distribution of cases and deaths from prostate cancer, between 2017 and 2020, in the 6 mesoregions of the state of Pará. All records of male patients with prostate cancer reported in the public domain database of DATASUS, under ―Hospital Morbidity of the SUS (SIH/SUS) were taken into account. Descriptive statistics, the chi-square test and the simple linear regression test were used for data analysis. Results: In the state of Pará, 57,591 cases of cancer were registered, regardless of the type and gender of involvement, with the capital Belém holding 33.33% of cases. Of these, 1083 cases refer to malignant neoplasm of the prostate, with Belém registering the highest number of cases (303; 28%), however in the period studied there was no trend of growth in the incidence rate of the disease (p=0.9448). There was a predominance of involvement of the elderly male population, brown men, mainly from 60 years old. A total of 163 deaths from prostate cancer were observed, with Belém comprising 77 deaths (47.23%) and having the third highest mortality rate from the disease (25.41%). However, there was no trend of growth in the mortality rate (p=0.1285). The metropolitan region of Belém was responsible for 59% of deaths from prostate cancer in the period. In addition, the number of deaths was more significant from the age of 60, with the age group of 80 years and over having a higher mortality rate (26.58%), and it is possible to notice a trend of growth in the mortality rate according to age (p=0.03). Brown men had more significant numbers of deaths (131; 80.36%), and the indigenous population had a crude mortality rate of 100%. Conclusion: More expressive numbers of prostate cancer are found mainly in the capital of Pará (Belém), with differences in involvement between the mesoregions. The elderly brown male population was the most affected. The incidence rate did not tend to grow in the period. The age group that most evolved to death was from the age of 60, with the highest mortality rate from the age of 80, with an increasing trend in the mortality rate according to the age group. Brown men had the highest number of deaths and the indigenous population the highest gross mortality rate.